2022
DOI: 10.7554/elife.70510
|View full text |Cite
|
Sign up to set email alerts
|

Pupil diameter is not an accurate real-time readout of locus coeruleus activity

Abstract: Pupil diameter is often treated as a noninvasive readout of activity in the locus coeruleus (LC). However, how accurately it can be used to index LC activity is not known. To address this question, we established a graded relationship between pupil size changes and LC spiking activity in mice, where pupil dilation increased monotonically with the number of LC spikes. However, this relationship exists with substantial variability such that pupil diameter can only be used to accurately predict a small fraction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 108 publications
5
84
0
Order By: Relevance
“…This assumption is often justified on the basis of the physiological findings that LC neurons spike at the time of salient events ( 8 ) and that LC activity or microstimulation precedes pupil dilation ( 11 , 12 ). Some highly cited papers thus claim that it is possible to infer activity in the LC-NE system from pupil size ( 52 ). This consensus model is nearly identical to one that has been used in functional magnetic resonance imaging (fMRI), in which the strength of neural activity is inferred by regressing a prediction, the convolution of the hemodynamic response function with impulses at trial event times, on the fMRI signal.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is often justified on the basis of the physiological findings that LC neurons spike at the time of salient events ( 8 ) and that LC activity or microstimulation precedes pupil dilation ( 11 , 12 ). Some highly cited papers thus claim that it is possible to infer activity in the LC-NE system from pupil size ( 52 ). This consensus model is nearly identical to one that has been used in functional magnetic resonance imaging (fMRI), in which the strength of neural activity is inferred by regressing a prediction, the convolution of the hemodynamic response function with impulses at trial event times, on the fMRI signal.…”
Section: Discussionmentioning
confidence: 99%
“…Long RTs can also result from involuntary bodily functions (e.g., sneezing or eye movements) or cases 3 Although the present work focuses on overt behavioral measures, recent research has also identified pupil diameter and its changes as potential physiological indicators of sustained attention . Pupil dilations may be indirectly related to LC-NE functioning (Aston-Jones & Cohen, 2005;Rajkowski et al, 1994; but see Megemont et al, 2022) which is linked to overall physiological arousal and attention.…”
Section: Limitations Of Objective Indicators Of Sustained Attentionmentioning
confidence: 99%
“…It is likely that the component of the ongoing pupil signal that is behaviorally relevant constitutes a small part of the signal. In fact, studies describing the association between neural activity and ongoing pupil dilation events report significant but small correlations suggesting that a large proportion of the pupil variance remains unexplained ( Joshi et al, 2016 ; Megemont et al, 2022 ; Reimer et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%